Can we predict amyloid deposition by objective cognition and regional cerebral blood flow in patients with subjective cognitive decline?. Issue 4 (27th January 2019) - Funaki, Kei; Nakajima, Shinichiro; Noda, Yoshihiro; Wake, Taisei; Ito, Daisuke; Yamagata, Bun; Yoshizaki, Takahito; Kameyama, Masashi; Nakahara, Tadaki; Murakami, Koji; Jinzaki, Masahiro; Mimura, Masaru; et al.
Abstract : Background: Subjective cognitive decline (SCD) may herald the first symptoms of Alzheimer's disease (AD) whereas individuals with beta‐amyloid (Aβ) deposition are regarded as a high‐risk group for AD. Recently, amyloid positron emission tomography (PET) studies have demonstrated clinical and cognitive feature differences between Aβ‐positive and negative SCD, but details of their differences remain unclear. We aimed to investigate the relationships among Aβ deposition, clinical, and cognitive features in patients with SCD. Methods: Forty‐two patients with SCD (22 women, 74.5 ± 4.7 years) were examined using fluorine‐18 florbetaben PET and were divided into Aβ‐positive (n = 10) and negative (n = 32) groups. We compared cognitive and psychological outcomes, and single photon emission computed tomography (SPECT) imaging data between the two groups. In addition, a linear regression analysis was performed to assess relationships between the severity of SCD and neuropsychological tests, affective scores, and demographic factors. Results: The rate of score changes from the immediate recall to delayed recall in the logical memory subtest of the Wechsler's Memory Scale Revised were different between the groups ( P = 0.04). However, the binary logistic regression analysis showed no significant differences between the two. In addition, the severity of SCD was significantly strong in women ( P = 0.002). Furthermore, within the Aβ‐negative group, subjective memory loss correlated with word fluency category score ( P = 0.023) and apathy scale ( P = 0.037). Conclusions: No significant differences were observed between Aβ‐positive and ‐negative SCD on any of the neuropsychological measures, clinical measures, or SPECT imaging. Further, the severity of SCD was not predicted by the symptoms of anxiety, depression, or neuropsychological examination.